2020
DOI: 10.31234/osf.io/75htx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semantic fluency reveals reduced functional connectivity between subcategorical co-hyponyms in recent-onset inpatients with first-episode psychosis

Abstract: In the wake of limited knowledge on clustering and switching during semantic fluency (SF) in patients with first-episode psychosis (PwFEP), the present study aimed (1) to investigate clustering and switching on SF in PwFEP using more precise statistical procedures and (2) to investigate the possibility of disproportionate clustering patterns across different SF tasks in PwFEP and healthy subjects (HS), as this has been indicated by the current literature on patients with schizophrenia. We recruited 22 PwFEP an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…On the other hand, this apparent language dominance imbalance might also be caused by the different letters and categories used in the English and French versions of the verbal fluency task. Research has suggested that speakers tend to produce more tokens overall in the "animals" category than in the "fruits" category (Moreno-Martínez et al, 2017;Gabrić and Vandek, 2020). Thus, the apparent language proficiency imbalance in favor of English might be caused by our use of an "easier" category in the testing of English proficiency.…”
Section: Methods Participantsmentioning
confidence: 99%
“…On the other hand, this apparent language dominance imbalance might also be caused by the different letters and categories used in the English and French versions of the verbal fluency task. Research has suggested that speakers tend to produce more tokens overall in the "animals" category than in the "fruits" category (Moreno-Martínez et al, 2017;Gabrić and Vandek, 2020). Thus, the apparent language proficiency imbalance in favor of English might be caused by our use of an "easier" category in the testing of English proficiency.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Discrepancies were discussed until mutual agreement was achieved. Clustering and switching variables were calculated according to Gabrić and Vandek (2021a).…”
Section: Methodsmentioning
confidence: 99%
“…It is clear from studies reporting descriptive data of multiple SF tasks that there are stark discrepancies in the number of legal words produced by healthy subjects across different semantic categories. Typically, adult healthy subjects produce the most words on animal fluency, while productivity on other semantic categories may be reduced by more than twofold (Bosanac et al, 2017; Gabrić & Vandek, 2021a; Jebahi et al 2020, 2021; Kim et al, 2015; Moreno-Martínez et al, 2017; Vicente et al, 2021). For example, Jebahi et al (2020) reported that subjects produced 18 words on average on animal fluency but less than ten on the categories accessories, tools, transportation means, furniture , and sports .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations